ANALISIS IMPLEMENTASI PROGRAM KELUARGA BERENCANA DI KECAMATAN PERCUT SEI TUAN - Lia Rosa Veronika Sinaga; Henny Arwina Bangun; Rahayu Agustina Pasaribu (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
Increasing population growth in Indonesia is a major problem facing the government. In addition, the weakening of the family planning program is not sufficient to solve the problem of population growth in Indonesia, so that the family planning program is established by the government whose goal is to form a healthy and prosperous family. The purpose of this study was to determine how the implementation of the family planning program in Percut Sei Tuan. This study uses a qualitative research method using a case study approach. Determination of informants using purposive sampling technique means that researchers select informants who are considered to know (key informants) in this study. The data collection techniques used were in-depth interviews, observation and documentation. Based on the Grindle theory which consists of several elements, including the interests of the target group, the types of benefits that can be obtained, the degree of change to be achieved, the location of decision making, program implementers, and resources that the implementation of the family planning program in Percut Sei Tuan has not fulfilled the six variables in this theory, such as there are still couples of childbearing age who do not want to participate in the implementation of the family planning program because they still believe that many children have a lot of sustenance, and are still afraid of disabilities when participating in the family planning program.